مستوى الرضا عن التخصص الأكاديمي لدى طلبة الجامعة - عمان, مسعودة; كتفي, عزوز (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة الحالية إلى الكشف عن مستوى الرضا عن التخصص الأكاديمي لدى طلبة الجامعة في ضوء تعدد تخصصات كلية العلوم الاجتماعية بجامعة الوادي وإذا ما كانت هناك فروق في مستواه تعزى للتخصص الدراسي حيث اعتمدت الدراسة الحالية على المنهج الوصفي في تقصيها للإشكال المطروح كما تم اختيار العينة بطريقة عشوائية قصديه حيث بلغت(54) طالبا وطالبة من مستوى سنة ثالثة ليسانس لبعض تخصصات كلية العلوم الاجتماعية كما تم جمع بيانات الدراسة باستخدام استبانه تقيس "الرضا عن التخصص الدراسي"من إعداد الباحثة نسيمة بن مبارك(2014). حيث توصلت نتائج الدراسة إلى أن مستوى الرضا عن التخصص الأكاديمي لدى طلبة الجامعة يتسم بالارتفاع كما توصلت الدراسة أيضا إلى وجود فروق دالة إحصائيا في مستوى الرضا عن التخصص الأكاديمي لدى طلبة كلية العلوم الاجتماعية تعزى لمتغير التخصص الدراسي لصالح تخصص الإرشاد والتوجيه. Abstract The current study aims to reveal the level of satisfaction with the academic specialization among university students in light of the multiplicity of specializations in the Faculty of Social Sciences at El-oued University, and if there are differences in its level attributable to the academic specialization, as the current study relied on the descriptive approach in its investigation of the proposed problem as the sample was chosen randomly I mean, as it reached (54) male and female students from the third year BA level for some specializations of the College of Social Sciences. The study data were also collected using a questionnaire measuring “satisfaction with academic specialization” prepared by researcher Nasima Bin Mubarak (2014), The results of the study concluded that the level of satisfaction with the academic specialization among university students is high. The study also found statistically significant differences in the level of satisfaction with the academic specialization among students of the College of Social Sciences due to the variable of the academic specialization.
في ضوء تعدد تخصصات كلية العلوم الاجتماعية
مقال
Keywords: رضا ; تخصص أكاديمي ; طالب جامعي; Satisfaction; Academic major; university studen